Changes in ther 2019-2020 competition season, in the national handball league, as a result of the COVID-19 pandemic - Gheorghe, C.; Mereutae, C. (Annals of "Dunarea de Jos" University of Galati: Physical Education and Sport Management, 2021)
The crisis launched by the COVID-19 had immediate consequences in all areas of activity, including the sports world. If initially in Romania the handball matches were played without spectators, then they were stopped, the players being forced to preventively isolate themselves at their homes. The first objective of this research is to identify and analyze the Romanian Handball Federation`s decisions taken at the beginning of the pandemic and the second objective is to identify the structural differences between a normal competitive season and the competitive season affected by the Covid-19 pandemic, in Romanian handball.